2018
DOI: 10.1111/jpn.12856
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of broilers’ caecal microflora and metabolites in response to a potential probiotic Bacillus amyloliquefaciens

Abstract: Studies have found that a dietary supplement of Bacillus amyloliquefaciens improved the growth performance, increased the nutrient digestibility of hosts and modulated the intestinal microflora. A total of 360 1-day-old Ross broilers were randomly divided into three treatments: a control group with a basal diet, an antibiotic group with a basal diet and added colistin sulphate, and a probiotics group with a basal diet and added Bacillus amyloliquefaciens. The HiSeq high-throughput sequencing analysis of 16S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 26 publications
1
37
0
2
Order By: Relevance
“…and reduced Escherichia coli levels in the intestinal contents of DFMsupplemented birds, compared with controls. Increased growth performance, nutrient utilization, and intestinal villus/crypt morphometry, as well as altered composition of gut microbiota, also were observed in chickens orally administered with Bacillus DFMs, compared with controls (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…and reduced Escherichia coli levels in the intestinal contents of DFMsupplemented birds, compared with controls. Increased growth performance, nutrient utilization, and intestinal villus/crypt morphometry, as well as altered composition of gut microbiota, also were observed in chickens orally administered with Bacillus DFMs, compared with controls (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 93%
“…Given the reported effects of DFMs on modulating the chicken gut microbiome (10)(11)(12), and the ability of intestinal bacteria to synthesize vitamins and nutrients beneficial to the host (43), it is somewhat surprising that few reports have examined the ability of DFMs to alter the avian metabolome (35,44). Cao et al (35) reported that dietary supplementation of chickens with B. amyloliquefaciens altered the levels of gut metabolites related to amino acid and glyceride metabolism. More specifically, increased levels of 4-aminobutyric acid, gentiobiose, quinic acid, 3,7,12-trihydroxycoprostane, N-ethylglycine, glycine, N-acetyl-D-galactosamine, and 5hydroxyindole-3-acetic acid, and reduced the levels of diglycerol and N-acetyl-β-D-mannosamine, were seen in the DFMsupplemented chickens, compared with unsupplemented controls.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond inherent basic nutrition, oral probiotics also exert many beneficial effects on health. Several species of Bacillus can function as antibiotic alternatives and growth promoters as they improve the digestibility and absorption of nutrients in the intestines of pigs and birds (Hong et al, 2005; Cao et al, 2018). Especially, emerging evidence has suggested that Bacillus amyloliquefaciens (BA) is beneficial for the amelioration of diarrhea and inflammation (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DFMs are also found to be suitable for chickens to reduce pathogen colonization and invasion in the intestinal tract to prevent several enteric infections such as Salmonella Enteritidis (14), E. coli (15), and Clostridium perfringens (16). Among the DFMs, Bacillus-based products have become more popular for potential use in broiler diets as alternatives to antibiotic growth promoters to improve both performance and health (17). Due to their spore-forming ability, these bacteria can withstand harsh environmental conditions including during feed processing and pelleting, as well as survive and germinate under conditions of the gastrointestinal tract (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus amyloliquefaciens is a spore-forming probiotic bacterium that produces a variety of extracellular enzymes including α-amylases, proteases, and phytase which could improve digestion and absorption of certain nutrients. Studies with Bacillus amyloliquefaciens have reported improved growth performance and villus morphology (20), modified cecal microbiota and metabolites (17), and increased serum IgG and IgA concentrations of healthy broilers (21). Li et al (22) suggested that dietary supplementation of Bacillus amyloliquefaciens downregulated mRNA abundance of TLR-4, INFγ, and IL-1β, and improved intestinal barrier junction in LPS-challenged broilers.…”
Section: Introductionmentioning
confidence: 99%